TRADISI â€œMETHILâ€ SEBAGAI SALAH SATU WARISAN KEARIFAN LOKAL DI DESA KARANGMALANG KECAMATAN KASREMAN KABUPATEN NGAWI - Septiana, Inka (ISSN.2252-8407)
Abstract Culture is performed by human activities. And human culture are two things that can not be separated from one another. In some cultures there is a tradition that is carried out by the community. The tradition contains human activities in implementing something such as bancaan ceremony just before the rice harvest. Modernization is a time machine that is able to change a pattern of human behavior even able to give effect to a change in the existing local culture. Villagers are able to maintain the local tradition to modernization era certainly have a very strong reason. Key words: traditional culture, society, tradition, and modernization Pendahuluan